Radical Solutions to the Housing Supply Crisis - Bowie, Duncan (Book collections on Project MUSE., 2017)
This book analyses the roots of the current housing crisis in England, critically reviewing the development of policy under successive UK Governments and presenting a specific critique of the current Conservative Government's housing and planning reforms.